Deep Endometriosis Induced Spontaneous Colon Rectal Perforation in Pregnancy: Laparoscopy Is Advanced Tool to Confirm Diagnosis - Aurelio Costa; Annalisa Sartini; Silvia Garibaldi; Marco Cencini (Case Reports in Obstetrics and Gynecology)
Endometriosis causes rare complications in pregnancy, such as obstetrical bleeding, preterm birth, spontaneous haemoperitoneum, and intestinal perforation. The prevalence of spontaneous perforation due to intestinal endometriosis is unknown in pregnancy. A recent review of the literature indicated 15 bowel complications caused by endometriosis during pregnancy or at the immediate postpartum period. The diagnosis of a bowel perforation can be difficult and in all of the cases reported necessitates an exploratory laparotomy. Anyway, in the majority of cases bowel perforation is not diagnosed during this laparotomy, and a repeat laparotomy is needed. Laparoscopy is being used increasingly in the diagnosis and operative management of acute abdomen. Laparoscopy can be a useful means of diagnosis and in addition a therapeutic tool in selected pregnant patients with abdominal pain. We report the first case of a pregnant woman with spontaneous double sigmoid and rectal perforation from decidualized endometriosis diagnosed by laparoscopy.